2000
DOI: 10.1302/0301-620x.82b7.10638
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in function after valgus bracing of the knee

Abstract: The use of a valgus brace can effectively relieve the symptoms of unicompartmental osteoarthritis of the knee. This study provides an objective measurement of function by analysis of gait symmetry. This was measured in 30 patients on four separate occasions: immediately before and after initial fitting and then again at three months with the brace on and off. All patients reported immediate symptomatic improvement with less pain on walking. After fitting the brace, symmetry indices of stance and the swing phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 0 publications
1
29
0
4
Order By: Relevance
“…The clinical effectiveness of this medical device has been reported in previous studies (i.a., [3][4][5][6][7][8]). However, studies published to date show conflicting results regarding the biomechanical mechanism of the knee brace.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical effectiveness of this medical device has been reported in previous studies (i.a., [3][4][5][6][7][8]). However, studies published to date show conflicting results regarding the biomechanical mechanism of the knee brace.…”
Section: Introductionmentioning
confidence: 99%
“…The results range from no effect to a significant improvement in gait symmetry and a reduction in external varus moments [2,5,[7][8][9][10]. A study using fluoroscopy during treadmill gait demonstrated articular surface separation at heel strike in subjects wearing valgus knee braces [11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most valgus braces offer little flexibility and there is a need for more adjustable braces. A new valgus brace, the SofTec OA brace (Bauerfeind GmbH), www.elsevier.com/locate/gaitpost Gait & Posture 26 (2007) [3][4][5][6][7][8][9][10] has been constructed with only a lateral hinge including an air chamber that enables adjustment of the valgus force by the patient (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollo et al [44] berichteten in einer Vergleichsstudie über eine deutliche Re duktion der Belastung im medialen Ge lenkkompartiment durch Valgusbracing, Minnich et al [37] konnten in einer Gan ganalysestudie mit getragenen Osteoarth roseorthesen nach 10 Wochen deutliche Verbesserungen des Gangbildes bei be troffenen Patienten nachweisen, die glei chen Resultate fanden Draper et al [10]. Das CochraneReview aus dem Jahre 2005 führt für valgisierende Knieorthesen eine nachgewiesene Verbesserung der Osteo arthrosesymptomatik auf und beschreibt den Stellenwert zur konservativen The rapie der Osteoarthrose als unbestritten.…”
Section: Technical Aids · Orthoses · Shoe Fittings · Walking Aids · Bunclassified